Semiotic approach to the media message and value exploration - hICHAM AKOUBACHE (Social Sciences Journal, 1970)
Semiotic research is almost absent from the media literature in the Arab region, and one of the justifications for this is the dominance of some epistemological models that were born in the confines of sociology and psychology, and defined from the beginning the parameters and frameworks of media research and how to address its problems. The behavioral positivist model is one of the most important and prominent of these models. This was embodied in what was later known as media influence research, as well as audience studies that depend mainly on collecting its data from the field (quantitative research), despite attempts to break with it through the efforts of critical and cultural studies and studies of reception with the traditional frameworks of media research that I inherited in the stage of inception. , However, she was unable to completely break free from these research patterns. Also, the research that focused on the media message was overshadowed by the Berlsonian vision regarding the procedural tools for analyzing its contents, so it was based on quantification, fragmentation of media texts and calculating the repetition of words at the most. Ignoring the qualitative methodology and its procedural tools, and its ability to analyze messages to memorize their different backgrounds and contexts, the active forces in them, and the modalities of producing and operating meanings. This falls within the so-called media discourse analysis studies, as well as semiotic studies of media content. The transformations that we are observing today at the level of the media scene in general, and the resulting new media phenomena that are not worthy of attention, such as: the dominance of the television image that resulted from the expansion and spread of the volume of direct satellite broadcasting, as well as the global network of information, and the high consumption of audiovisual messages at the expense of read messages. The emergence of new media with its applications and practices as a result of information and communication technologies. Hence, reading and studying these contents requires a new vision to reveal their social and cultural loads and belts, and we think that the semiotic approach presents itself as a research project that can cover some areas that were overlooked or that previous visions stood helpless in front of it, especially with regard to non-verbal expressions in the widespread fixed and animated media images. in the media; Semiotics from this side seeks to dismantle symbols and icons in order to show the values inherent in media products, which we aim to show through this research paper and for that: We had a pause with the current media studies and research, through which we highlighted the limits of research in media and communication sciences at the time The current as well as the theoretical backgrounds that control the study of its various problems, then we were exposed to the curricula of media sciences, specifically the quantitative and qualitative approaches and their respective uses, as we explained the gaps in quantitative research and the criticisms that were exposed to it and the reasons for ignoring qualitative research in the field of media. Then we moved to the second part of this research paper, which is the semiotic approach to the media message, in which we defined the concept of semiotics and its meaning. Scientific and serious about media contents and media sciences in general. Finally, we showed how the semiotic approach, through its tools, can deconstruct the values inherent in the media message, taking advertising as a model.